2012
DOI: 10.1111/j.1542-4758.2012.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modality change on health‐related quality of life

Abstract: Background Patients with ESRD requiring renal replacement have impaired quality of life (HRQoL), and there is general consensus that HRQoL improves with successful transplant and evidence of improvement with frequent hemodialysis. This study reports changes in HRQoL associated with changes in treatment modality to daily hemodialysis (DHD) and transplant among patients requiring renal replacement. Methods This cohort study had assessments at baseline and 6-months following modality change. Subjects were non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…Successful renal replacement therapy leads to good quality of life (QOL). Hemodialysis is the most popular renal replacement therapy (Painter, Krasnoff, Kuskowski, Frassetto, & Johansen, 2012). In fact, the advent of efficient hemodialysis techniques was associated with a significant extension to a patient's life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Successful renal replacement therapy leads to good quality of life (QOL). Hemodialysis is the most popular renal replacement therapy (Painter, Krasnoff, Kuskowski, Frassetto, & Johansen, 2012). In fact, the advent of efficient hemodialysis techniques was associated with a significant extension to a patient's life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] A number of studies have indicated that the QOL of dialysis patients is greatly impaired compared to general population. 10,11 However, differences in QOL between PD and HD patients have not been clearly identified. Few studies have examined the factors contributing to QOL of dialysis patients in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…The SF-36 is an instrument that uses 36 questions to assess health-related quality of life (HRQoL) that has previously been used in patients with ESRD [20,21]. The Physical Function scale (PF) is a subscale of the SF-36 that uses ten items that are hierarchically ordered to assess physical function.…”
Section: Methodsmentioning
confidence: 99%